Preparation of Manganese Dioxide Nanoparticles on Laterite for Methylene Blue Degradation - Thu-Huong Le; Thu Hong Anh Ngo; Van Thuan Doan; Le Minh Tri Nguyen; Manh Cuong Le (Journal of Chemistry)
The laterite-coating manganese dioxide nanoparticle material (M2) prepared by the immersion method was used for the efficient removal of methylene blue (MB) from aqueous solution. The adsorption and heterogeneous Fenton catalytic oxidation experiments of M2 were investigated by changing the effective factors such as time, pH, amount of M2, and concentration of MB. The adsorption data of M2 showed good fitting with the Langmuir isotherm, suggesting that the adsorption of MB on the surface of M2 is a heterogeneous and physical adsorption process. Degradation of MB was also carried out to evaluate the heterogeneous Fenton catalytic oxidation characterization of a new catalytic oxidation material (M2). The results show that the M2 material has both adsorption and heterogeneous Fenton catalytic oxidation. However, the heterogeneous Fenton catalytic oxidation of the M2 material is the main performance. Hence, our groups have investigated the ability of the catalytic column treatment with high efficiency of 98–100% and the degradation efficiency after the sample running through the column almost does not change much. This proves that heterogeneous Fenton catalytic activity of the catalytic column is completely unaffected and reused many times after oxidizing MB. Specifically, even if the M2 material is reused for five times, the degradation efficiency still reaches 98.86%.